BRS Novo Horizonte - a new cassava variety for industrial use - Oliveira,Eder Jorge de (2020)
Abstract The new cassava variety ‘BRS Novo Horizonte’ was developed and released in Bahia, Brazil for industrial use, particularly for starch production. The fresh and dry root yields were 39% and 44% higher, respectively, than those of local varieties. The root quality traits allowed the extraction of high-quality starch. The variety is also adapted for mechanized cropping systems.